The Effectiveness of Technology-Based Human Resource Management in Enhancing Teacher Professionalism in Vocational High Schools - Dyah Ayuningtiyas (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2026)
The digital transformation in education requires schools to adopt more adaptive and technology-based management systems. This study aims to analyze the effectiveness of technology-based human resource management (HRM) in enhancing teacher professionalism at SMK Miftahul Ulum Cimerak. A descriptive qualitative approach was employed, utilizing observation, in-depth interviews, and documentation as data collection techniques. The results indicate that the application of digital systems in HRM such as personnel management platforms, online training, and technology-based performance evaluation has improved work efficiency, accountability, and teachers’ professional competence. Despite challenges such as limited digital skills among some teachers, transformative leadership and internal collaboration have become key supporting factors for successful implementation. The study recommends strengthening continuous training strategies to optimize technology integration in the educational sector.